H1-receptor antagonisták ödémagátló hatása [Anti-oedematous effects of some H1-receptor antagonists] - Rázga Zsolt (ACTA PHARMACEUTICA HUNGARICA, 1991)
Experiments carried out with mice of CFLP strain have shown that antihistaminics (chloropyramine, cyproheptadine and dimethindene maleate) significantly inhibit the extents of ear oedema induced by croton oil, dithranol or capsaicin. In rats of Wistar strain, oedema was induced in the hind paw by the subplantar injection of carrageenin, and simultaneously by the application of croton oil to the inner surface on the ear. Preliminary antihistamine treatment inhibited the development of both types of oedema, to statistically significant extent.